Pengolahan Sampah Organik dari Limbah Rumah Tangga Menjadi Produk Eco-Enzyme di Desa Dalaka Kabupaten Donggala - Ruslan, Ruslan; Khairuddin, Khairuddin; Hardi, Jaya (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to increase the knowledge and skills of housewives in Dalaka Village by processing organic waste from household waste into eco-enzyme products. This service was implemented through counseling and training in making fermenters and making eco-enzymes with simple and inexpensive methods. The production of eco-enzymes was done using the ratio of 3kg of organic waste, 1 kg of brown sugar, and 10L of water. The instrument for evaluating this activity used a satisfaction questionnaire form and was analyzed descriptively. The results of this dedication showed that partners could understand well the technology introduced and apply it. The resulting eco-enzyme product had a brown color and a distinctive sour aroma. The average level of participant satisfaction was in the "satisfied" range. Utilization of organic waste from household